2018
DOI: 10.15296/ijwhr.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Glance at Domestic Violence Phenomenon in Early Marriages: A Narrative Review

Abstract: Objectives: Teenage marriage results in social, cultural, and economic problems including domestic violence. Based on research evidence, the present study attempted to provide a documentary image of domestic violence in early marriages. Materials and Methods: This study was conducted by searching different databases such as Web of Science, Cochrane Library, Science Direct, PubMed, Scientific Information Database, Google Scholar, Magiran, Irandoc, and Iranmedex for articles which were published during 2000-2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…The results of a study consistent with our study indicated that marital satisfaction among students with early marriages was moderate [34]. Another study reported that with early marriage in the golden years of life, young women would become victims of violence, causing the most damage [35]. Chauhan et al's study in India showed that men belonging to high-income families were more satis ed with their marriages.…”
Section: Discussionsupporting
confidence: 89%
“…The results of a study consistent with our study indicated that marital satisfaction among students with early marriages was moderate [34]. Another study reported that with early marriage in the golden years of life, young women would become victims of violence, causing the most damage [35]. Chauhan et al's study in India showed that men belonging to high-income families were more satis ed with their marriages.…”
Section: Discussionsupporting
confidence: 89%
“…(Sezgin & Punamäki, 2020). Low level of education of women, lack of economic independence, and getting married at an early age are the main reasons that increase violence (Sattarzadeh et al, 2019). Marital conflicts, economic problems, unemployment for more than 6 months, and negative life experiences in the last 12 months are risk factors for the development of depression (Fakhari et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…16 In there has been an increase in violence in some cases, a decrease in violence in others, and no connection with violence in some cases. 17 As can be seen from the studies, the majority of these studies have investigated the various dimensions of violence and the consequences associated with it, while an aspect related to the socioeconomic index has not been investigated. 18 The socioeconomic status of the household is regarded as one of the most important variables influencing domestic violence.…”
Section: Introductionmentioning
confidence: 99%
“…In reviewing the research done in Iran on this subject, various factors have been found to be effective in relation to domestic violence and in reducing or increasing it, such as increasing age, 14 higher education for women, 15 and female employment 16 . In there has been an increase in violence in some cases, a decrease in violence in others, and no connection with violence in some cases 17 …”
Section: Introductionmentioning
confidence: 99%